Can the internet buy working hours of married women in micro and small enterprises? Evidence from Yogyakarta, Indonesia - Eny Sulistyaningrum; Budy P. Resosudarmo; Anna T. Falentina; Danang A. Darmawan (Asian Development Bank Institute (ADBI), 2021)
The development of information and communication technology (ICT) has totally changed, especially in relation to the use of the internet. Smartphones play an important role as media for using the internet. Today, with the rapid development of ICT, almost everyone has a smartphone with good access to the internet. People have started to expand the use of smartphones not only for leisure but also for business. This change in internet usage also affects the labor market significantly. Individuals who prefer to stay at home rather than work outside will try to do some business at home. This business usually generates micro and small enterprises (MSEs). The number of MSEs that are digitalizing their business is increasing significantly. They utilize every single digital tool they can, such as websites, social media, web email, and other online marketplaces. Married women, who typically reduce the time they allocate to work due to their responsibility to take care of their children, can also now make money from home easily. By using micro survey data from our field survey in the city of Yogyakarta and Bantul district in January 2018, this paper investigates the impact of internet access on the working hours of married women who are the owners or managers of MSEs and also the probability of working for them. We employ IV estimates, and use the Telkomsel signal as the instrument variable. From the first stage estimation, it can be seen that the Telkomsel signal is a strong instrument. The findings suggest that internet access has a significant impact on increasing the daily working hours of married women. In addition, we find that married women in urban areas increase their working hours when they obtain internet access more than married women in rural areas.
Keywords: J20; J21; J22; 330; internet; married women; working hours; IV; MSE